2002
DOI: 10.1105/tpc.010258
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Damaged DNA by Arabidopsis Cell Extract

Abstract: All living organisms have to protect the integrity of their genomes from a wide range of genotoxic stresses to which they are inevitably exposed. However, understanding of DNA repair in plants lags far behind such knowledge in bacteria, yeast, and mammals, partially as a result of the absence of efficient in vitro systems. Here, we report the experimental setup for an Arabidopsis in vitro repair synthesis assay. The repair of plasmid DNA treated with three different DNA-damaging agents, UV light, cisplatin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 52 publications
1
43
1
Order By: Relevance
“…Surprisingly the AtRAD1 gene, encoding an endonuclease, which together with Rad10p (ERCC1) is involved in the 59 incision of the UV damage, was found to be upregulated in the Atcen2 plants compared with the control. These results are in apparent conflict with the work of Fidantsef et al (2000) and Li et al (2002) who have shown that RAD1-deficient Arabidopsis plants exhibited higher UV-C sensitivity and reduced efficiency of dark repair of UV-induced DNA damage. Therefore, our data suggest that the increased load of damage, because of downregulation of photolyase and to lower NER efficency, may be responsible for the increased Rad1 mRNA level.…”
Section: Why Do Atcen2 Plants Exhibit a Hyperrecombinogenic Phenotype?contrasting
confidence: 55%
See 3 more Smart Citations
“…Surprisingly the AtRAD1 gene, encoding an endonuclease, which together with Rad10p (ERCC1) is involved in the 59 incision of the UV damage, was found to be upregulated in the Atcen2 plants compared with the control. These results are in apparent conflict with the work of Fidantsef et al (2000) and Li et al (2002) who have shown that RAD1-deficient Arabidopsis plants exhibited higher UV-C sensitivity and reduced efficiency of dark repair of UV-induced DNA damage. Therefore, our data suggest that the increased load of damage, because of downregulation of photolyase and to lower NER efficency, may be responsible for the increased Rad1 mRNA level.…”
Section: Why Do Atcen2 Plants Exhibit a Hyperrecombinogenic Phenotype?contrasting
confidence: 55%
“…To test this directly, cell extracts of P2.4, RNAi, and IC9 plants were used in the in vitro DNA repair assay described by Li et al (2002). This assay measures the efficiency of incorporation of DIG dUTP in a UV-C damaged plasmid in the presence of plant cell extracts.…”
Section: Efficiency In Repair Of Uv-c Damaged Dnamentioning
confidence: 99%
See 2 more Smart Citations
“…Simpson and Sale (2003) suggested that Rev1 and TLS are critical for efficient tolerance or repair of ICLs and that it is likely involved in other pathways. In higher plants, many genes involved in NER and recombinant repair have been isolated, and some of them were found to be involved in tolerance to DNA cross-linkers (Xu et al, 1998;Li et al, 2002). Therefore, it is possible that TLS works synergistically with NER and/or recombinant repair in plants.…”
Section: Discussionmentioning
confidence: 99%